Options to overcome the barriers to pricing European agricultural emissions. (7th February 2018) - Grosjean, Godefroy; Fuss, Sabine; Koch, Nicolas; Bodirsky, Benjamin L.; De Cara, Stéphane; Acworth, William
ABSTRACT: Although agriculture could contribute substantially to European emission reductions, its mitigation potential lies untapped and dormant. Market-based instruments could be pivotal in incentivizing cost-effective abatement. However, sector specificities in transaction costs, leakage risks and distributional impacts impede its implementation. The significance of such barriers critically hinges on the dimensions of policy design. This article synthesizes the work on emissions pricing in agriculture together with the literature on the design of market-based instruments. To structure the discussion, an options space is suggested to map policy options, focusing on three key dimensions of policy design. More specifically, it examines the role of policy coverage, instruments and transfers to farmers in overcoming the barriers. First, the results show that a significant proportion of agricultural emissions and mitigation potential could be covered by a policy targeting large farms and few emission sources, thereby reducing transaction costs. Second, whether an instrument is voluntary or mandatory influences distributional outcomes and leakage. Voluntary instruments can mitigate distributional concerns and leakage risks but can lead to subsidy lock-in and carbon price distortion. Third, the impact on transfers resulting from the interaction of the Common Agricultural Policy (CAP) with emissions pricing will play a key role in shaping political feasibility and has so far been underappreciated. POLICY RELEVANCE Following the 2015 Paris Agreement, European climate policy is at a crossroads. Achieving cost-effectively the 2030 and 2050 European targets requires all sectors to reduce their emissions. Yet, the cornerstone of European climate policy, the European Union Emissions Trading System (EU ETS), covers only about half of European emissions. Major sectors have been so far largely exempted from carbon pricing, in particular transport and agriculture. While transport has been increasingly under the spotlight as a possible candidate for an EU ETS sectoral expansion, policy discussions on pricing agricultural emissions have been virtually absent. This article attempts to fill this gap by investigating options for market-based instruments to reduce agricultural emissions while taking barriers to implementation into account.